The Diversity of Butterflies (Lepidoptera) in the Aik Bukak Tourism Park Area - Rizka Yulia Ashari; Moh. Liwa Ilhamdi; Didik Santoso (Jurnal Biologi Tropis, 2022)
Butterflies have an important role in human life in various fields such as ecology, economy, aesthetics, and education. The Aik Bukak Tourism Park area is one of the butterfly habitats in Aik Bukak Village, Batu Kliang Utara District, Central Lombok Regency. That aims to determine the diversity of butterflies in the Aik Bukak Tourism Park area. Data collection used a purposive survey method with a sweeping technique following three predetermined observation lines, namely the entrance, the path around the pond, and the forest path. This research was fully recorded 327 individuals member of 23 spesies, 18 genera, and 5 families. The analysis of the butterfly species diversity index used the Shannon-Wienner formula and the diversity index value (HÃâº) was 2.939 which means medium category. The species dominance index was analyzed using the Simpson's species dominance formula and obtained the species dominance index value was 0.059, which means that no species dominates at that location.